Staggered enforcement of infection control and prevention measures following four consecutive potential laboratory exposures to imported Brucella melitensis. Issue 2 (June 2021) - Miendje Deyi, V.Y.; Mori, M.; Dauby, N.; Clevenbergh, P.; Mahadeb, B.; Loizidou, A.; Maillart, E.; Martiny, D.; Debyttere, A.L.; Gerard, M.; Hallin, M.
Summary: From 2015 until 2020, Brucella melitensis was isolated four times in our microbiology laboratory. All patients had travelled in endemic-areas. Immediately after the first occurrence, all laboratory staff were risk-stratified and preventive and protective measures were applied according to CDC guidelines. Nineteen workers were exposed and needed chemoprophylaxis and follow-up. At each subsequent occurrence, risk analysis was performed, and additional measures were implemented accordingly, leading to a progressive reduction of exposed staff members to none the fourth time. We describe here the additional measures that permitted this important exposure reduction.